Starch-based degradable composite material film
By modifying plant starch and adding compatibility aids, the compatibility between starch and polyester materials is improved, and the problems of low starch content and insufficient performance of starch-based composite materials in the prior art are solved, and composite film preparation with high starch content, low cost and good mechanical properties are achieved.
Patent Information
- Application Number
- CN202311410385.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-10-27
- Publication Date
- 2025-04-29
- Estimated Expiration
- 2043-10-27
AI Technical Summary
In the prior art, the starch content of the starch-based composite material is low, resulting in high material cost and insufficient performance, and poor compatibility between starch and polyester, making it difficult to improve the starch content and material performance.
By modifying plant starch with polyurethane prepolymers, changing its molecular structure, improving compatibility with polyester materials, and adding compatibility additives to improve material performance, finally a composite film with high starch content is prepared through a film blowing process.
It realizes a composite material with high starch content, reduces material costs, and maintains good mechanical properties and high compatibility, and is suitable for large-scale industrial production.
Smart Images

Figure BDA0004517990130000021 
Figure BDA0004517990130000041 
Figure BDA0004517990130000042
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of polymer materials, and in particular to a low-cost, high-proportion plant starch / two-component polymer polyester composite biodegradable film and a preparation method thereof. Background Art
[0002] Plastics are widely used in packaging bags, mulch films, and disposable tableware due to their low cost, high mechanical properties, and easy processing. However, traditional non-degradable plastics are mainly made of petroleum-based materials such as polyethylene. In addition to being non-renewable and limited in resources, their excessive use may lead to the accumulation of solid waste. A large amount of "white pollution" will not only harm land resources, but also cause a large amount of plastic waste to accumulate in the marine environment, and due to its non-degradability, it will cause serious harm to the natural environment on which humans depend for survival.
[0003] Starch is not only an abundant, low-cost resource with high renewability and biodegradability, but its degradation products are also beneficial to plant growth and do not cause risks such as soil compaction or seawater pollution. This shows that starch-based materials are suitable to replace petroleum-based plastics and become one of the raw materials for the preparation of new degradable materials.
[0004] In industrial production, in order to optimize production factors such as output and cost, the blown film process is usually used to blow composite materials. However, due to the lack of thermoplastic properties of starch and its low processability, pure starch materials cannot be blown into films. At present, starch-based composite materials prepared by blending with degradable polyesters such as polybutylene adipate (PBAT) and polylactic acid (PLA) are promising degradable composite materials that can overcome the limitations of starch's own performance when used in the blown film process to a certain extent, and at the same time can reduce the material cost of pure degradable polyester materials as film products.
[0005] Currently, many researchers prepare composite films by blending starch and degradable polyester, but the starch content in the composite film is relatively low. The higher the starch content, the lower the cost of the composite material, but the material performance will decrease, and the processing difficulty will increase. More importantly, as the starch content increases, starch and polyester are often difficult to mix evenly. The hydrophilic properties of starch materials and the hydrophobic properties of polyester materials make the two extremely incompatible. Increasing the starch content of composite materials, enhancing the interface bonding between starch and polyester, and continuous preparation play a vital role in the development of starch-based degradable materials. Summary of the invention
[0006] The purpose of the present invention is to solve the problems existing in the prior art and to study low-cost biodegradable materials. A plant starch / polymer polyester composite biodegradable film with a high starch content and a preparation method thereof are provided. The film not only maintains the good mechanical properties of the material, but also increases the starch content in the composite material, thereby greatly reducing the cost of the composite material.
[0007] In order to achieve the above object, the present invention adopts the following technical solutions:
[0008] In a first aspect of the present invention, a starch-based plastic film is provided, which is a plant starch / polymer polyester composite biodegradable material film, comprising the following components:
[0009]
[0010] In another preferred embodiment, the starch-based plastic film of the present invention is composed of plant starch, composite polyester, polyurethane prepolymer, compatibility aid, reinforcing agent, and lubricant, and is obtained through the preparation process of mixing, twin-screw extrusion blending, and blow molding.
[0011] In another preferred embodiment, the plant starch is at least one of potato starch, corn starch, wheat starch, tapioca starch and pea starch.
[0012] In another preferred embodiment, the weight proportion of the plant starch is 30-65, 30-60 or 35-55.
[0013] In another preferred embodiment, the plant starch used in the present invention has an amylose content of more than 15 wt % and a water content of less than or equal to 11 wt %.
[0014] In another preferred embodiment, the polyurethane prepolymer is prepared by reacting one of polyethylene adipate glycol, polycaprolactone glycol, polytetramethylene ether glycol, polybutylene adipate glycol and polybutylene succinate glycol with one of diphenylmethane diisocyanate, hexamethylene diisocyanate and toluene diisocyanate.
[0015] In another preferred embodiment, the isocyanate content of the polyurethane prepolymer is 3wt%-10wt%.
[0016] In another preferred embodiment, the polyurethane prepolymer is 5-15 parts by weight or 5-12 parts by weight.
[0017] In another preferred example, the composite polyester comprises polybutylene adipate / terephthalate (PBAT) and polylactic acid (PLA), wherein the mass percentage of PBAT is 70%-99% of the total amount of the composite polyester material, and the mass percentage of PLA is 30%-1% of the total amount of the composite polyester material.
[0018] Polybutylene adipate / terephthalate (PBAT) and polylactic acid (PLA) are the two most widely used biodegradable polyester materials in industry. PBAT has excellent toughness and ductility and good elongation at break, while PLA has good rigidity and good tensile strength.
[0019] Further preferably, the mass percentage of PBAT is 75%-95% of the total amount of the composite polyester material, and the mass percentage of PLA is 25%-5% of the total amount of the composite polyester material.
[0020] Further preferably, the mass percentage of PBAT is 80%-92% of the total amount of the composite polyester material, and the mass percentage of PLA is 20%-8% of the total amount of the composite polyester material.
[0021] In another preferred embodiment, the composite polyester is 35-50 parts by weight.
[0022] Further preferably, the compatibilizer is at least one of citric acid, maleic anhydride, chain extension PBAT, (Jia Yirong) chain extension SAG-008, (BASF) chain extension ADR-4370, (BASF) chain extension ADR4468, (Shanxi Chemical) chain extension KL-E4370, KL-E4370B, (Coais) chain extension KS-05, and (Shanghai Xiuyuan) chain extension XY4370.
[0023] In another preferred embodiment, the compatibilizer is a chain extender.
[0024] In another preferred embodiment, the compatibilizer is 0.8-6 or 1-3 parts by weight.
[0025] Further preferably, the plant starch is at least one of corn starch, wheat starch, cassava starch, potato starch and pea starch, and the plant starch has an amylose content of more than 15% and a moisture content of less than or equal to 11%.
[0026] More preferably, the reinforcing agent is at least one of attapulgite, halloysite, nano silicon dioxide, nano calcium carbonate, nano zinc oxide, montmorillonite and bentonite.
[0027] In another preferred embodiment, the reinforcing agent is 0.8-4 or 1-3 parts by weight.
[0028] More preferably, the lubricant is at least one of Tween, calcium stearate, magnesium stearate, erucic acid amide, erucic acid amide, and docosenoic acid amide.
[0029] In another preferred embodiment, the lubricant is 0.5-1.5 or 0.5-1 parts by weight.
[0030] In the film prepared in the present invention, at least one of the chain extender and prepolymer content is not zero.
[0031] In another preferred embodiment, the starch-based plastic film is a plant starch / polymer polyester composite biodegradable material film, comprising the following components:
[0032]
[0033] In another preferred embodiment, the starch-based plastic film is a plant starch / polymer polyester composite biodegradable material film, comprising the following components:
[0034]
[0035] The second aspect of the present invention provides a method for preparing the starch-based plastic film according to the first aspect, comprising the following steps:
[0036] S1: Dry the plant starch and store it in a sealed container for later use;
[0037] S2: Put the dried plant starch into an internal mixer, add the polyurethane prepolymer, modify the plant starch, use a pulverizer to process the modified starch into particles of 20-60 meshes, and seal and store them for later use;
[0038] S3: putting the modified starch granules obtained in S2 into a high-speed mixer, adding the composite polyester, and then adding the compatibilizer, reinforcing agent, and lubricant, mixing evenly and then taking out for use;
[0039] S4: adding the mixed material prepared in S3 into a twin-screw extruder for extrusion, and then drawing, water-cooling, and granulating on a twin-screw auxiliary machine to obtain a light yellow cylindrical granular material;
[0040] S5: drying the granular material obtained in S4 and adding it to a film blowing machine for film blowing, and obtaining a starch-based biodegradable film through a winding device.
[0041] In another preferred embodiment, the plant starch is dried in an oven at 60° C.-80° C. for 3-6 hours.
[0042] In another preferred embodiment, the temperature in the internal mixer is set at 80° C.-100° C., and the mixing time is 20 min-45 min.
[0043] In another preferred embodiment, the modified starch uniformly mixed in the internal mixer is taken out and placed at room temperature for 12 hours to 24 hours.
[0044] In another preferred embodiment, the temperature in the high-speed mixer is controlled at 20° C.-40° C., and the mixing time is 5 min-15 min.
[0045] In another preferred embodiment, the temperature of the feeding section of the twin-screw extruder is set to 120°C-130°C, the temperature of the middle section is set to 130°C-155°C, and the temperature of the head section is set to 140°C-160°C.
[0046] In another preferred embodiment, the granular material obtained in S4 is dried in an oven for 4h-6h, and the temperature in the oven is 60°C-80°C.
[0047] In another preferred embodiment, the temperature of the die head of the film blowing machine in S5 is 140°C-160°C, the body temperature is 130°C-155°C, and the film blowing temperature is 140°C-150°C.
[0048] In a preferred embodiment, the preparation method of the present invention comprises the following steps:
[0049] S1: Dry the plant starch granules in an oven at 60°C-80°C for 3-6 hours and seal them for later use;
[0050] S2: Put the dried plant starch into an internal mixer, add polyurethane prepolymer, and modify the plant starch. The temperature in the internal mixer is set at 80°C-100°C, and the mixing time is 20min-45min. Take out the evenly mixed modified starch, and place it at room temperature for 12h-24h. Use a pulverizer to process the modified starch into particles of 20-60 mesh size, and seal it for storage for later use.
[0051] S3: Put the modified starch granules obtained in S2 into a high-speed mixer, add the PBAT / PLA masterbatch mixture, and then add the compatibilizer, reinforcing agent, and lubricant. The temperature in the high-speed mixer is controlled at 20℃-40℃, the mixing time is 5min-15min, and after mixing evenly, take out for use.
[0052] S4: Add the prepared mixed material into the twin screw, set the temperature of each zone, set the temperature of the feeding section to 120℃-130℃, the temperature of the middle section to 130℃-155℃, and the temperature of the head part to 140℃-160℃, then pull the strips, water cool and granulate on the twin screw auxiliary machine to obtain light yellow cylindrical granular raw materials.
[0053] S5: Dry the granular material obtained in S4 in an oven for 4h-6h, the temperature in the oven is 60℃-80℃, and add the dried raw material into a film blowing machine for film blowing.
[0054] S6: In S5, the temperature of the die head is 140°C-160°C, the temperature of the machine body is 130°C-155°C, and the film blowing temperature is 140°C-150°C. The starch-based degradable film is obtained by the winding device.
[0055] In another preferred embodiment, the addition amount of each component is as follows:
[0056]
[0057] In another preferred embodiment, the plant starch is at least one of potato starch, corn starch, wheat starch, tapioca starch and pea starch.
[0058] In another preferred embodiment, the weight proportion of the plant starch is 45-65, 40-60 or 35-55.
[0059] In another preferred embodiment, the plant starch used in the present invention has an amylose content of more than 15 wt % and a water content of less than or equal to 11 wt %.
[0060] In another preferred embodiment, the polyurethane prepolymer is prepared by reacting one of polyethylene adipate glycol, polycaprolactone glycol, polytetramethylene ether glycol, polybutylene adipate glycol and polybutylene succinate glycol with one of diphenylmethane diisocyanate, hexamethylene diisocyanate and toluene diisocyanate.
[0061] In another preferred embodiment, the isocyanate content of the polyurethane prepolymer is 3wt%-10wt%.
[0062] In another preferred embodiment, the polyurethane prepolymer is 5-15 parts by weight or 5-12 parts by weight.
[0063] In another preferred example, the composite polyester comprises polybutylene adipate / terephthalate (PBAT) and polylactic acid (PLA), wherein the mass percentage of PBAT is 70%-99% of the total amount of the composite polyester material, and the mass percentage of PLA is 30%-1% of the total amount of the composite polyester material.
[0064] Polybutylene adipate / terephthalate (PBAT) and polylactic acid (PLA) are the two most widely used biodegradable polyester materials in industry. PBAT has excellent toughness and ductility and good elongation at break, while PLA has good rigidity and good tensile strength.
[0065] Further preferably, the mass percentage of PBAT is 75%-95% of the total amount of the composite polyester material, and the mass percentage of PLA is 25%-5% of the total amount of the composite polyester material.
[0066] Further preferably, the mass percentage of PBAT is 80%-92% of the total amount of the composite polyester material, and the mass percentage of PLA is 20%-8% of the total amount of the composite polyester material.
[0067] In another preferred embodiment, the composite polyester is 35-50 parts by weight.
[0068] Further preferably, the compatibilizer is at least one of citric acid, maleic anhydride, chain extension PBAT, (Jia Yirong) chain extension SAG-008, (BASF) chain extension ADR-4370, (BASF) chain extension ADR4468, (Shanxi Chemical) chain extension KL-E4370, KL-E4370B, (Coais) chain extension KS-05, and (Shanghai Xiuyuan) chain extension XY4370.
[0069] In another preferred embodiment, the compatibilizer is a chain extender.
[0070] In another preferred embodiment, the compatibilizer is 0.8-6 or 1-3 parts by weight.
[0071] Further preferably, the plant starch is at least one of corn starch, wheat starch, cassava starch, potato starch and pea starch, and the plant starch has an amylose content of more than 15% and a moisture content of less than or equal to 11%.
[0072] More preferably, the reinforcing agent is at least one of attapulgite, halloysite, nano-silicon dioxide, nano-calcium carbonate, nano-zinc oxide, montmorillonite and bentonite.
[0073] In another preferred embodiment, the reinforcing agent is 0.8-4 or 1-3 parts by weight.
[0074] More preferably, the lubricant is at least one of Tween, calcium stearate, magnesium stearate, erucic acid amide, erucic acid amide, and docosenoic acid amide.
[0075] In another preferred embodiment, the lubricant is 0.5-1.5 or 0.5-1 parts by weight.
[0076] In the film prepared in the present invention, at least one of the chain extender and prepolymer content is not zero.
[0077] The present invention comprises at least the following advantages:
[0078] First, the present invention utilizes polyurethane prepolymer to modify plant starch, thereby reducing the number of hydrophilic hydroxyl groups on the long chain of starch and simultaneously reducing the number of hydrogen bonds in starch molecules, thereby changing the original molecular structure of starch and improving the compatibility between starch material and polyester material.
[0079] Second, the present invention improves the compatibility between starch, PBAT and PLA by using a compatibility aid, and greatly improves the material performance, thereby providing a performance basis for starch-based materials with a high starch content, making it possible to increase the starch content in composite materials.
[0080] Third, the prepolymer and compatibility additive bring better compatibility to the composite material, resulting in a more uniform and smooth surface morphology, and can still maintain good mechanical properties under the premise of high starch content. Its tensile strength can exceed 16MPa and its elongation at break can reach 931%.
[0081] Fourth, the starch-based degradable film prepared by the method of the present invention has better degradation performance than general starch-based films, and also overcomes the problems of processing difficulties and poor hydrophobicity, and is suitable for large-scale industrial production. The product is environmentally friendly, and its degradation rate can exceed 90wt% within 90 days.
[0082] It should be understood that within the scope of the present invention, the above-mentioned technical features of the present invention and the technical features specifically described below (such as embodiments) can be combined with each other to form a new or preferred technical solution. Each feature disclosed in the specification can be replaced by any alternative feature that provides the same, equal or similar purpose. Due to space limitations, they will not be described one by one here. BRIEF DESCRIPTION OF THE DRAWINGS
[0083] Figure 1 The mechanical properties test results are shown.
[0084] Figure 2 This is a scanning electron microscope image.
[0085] Figure 3 The film blowing process is shown.
[0086] Figure 4 Shows the morphology of the film. DETAILED DESCRIPTION
[0087] The inventor has prepared a modified starch without hydrophilic properties by means of prepolymer modification through extensive and in-depth research, and then compounded it with polyester materials (polybutylene adipate / terephthalate PBAT and polylactic acid PLA). The compatibility between starch, PBAT and PLA materials is improved by adding a compatibility aid, and a starch / PBAT / PLA composite material with excellent performance is prepared by combining the advantages of the three materials. Finally, the prepared composite material is blown by a film blowing process to prepare a starch / PBAT / PLA film material. On this basis, the present invention has been completed. The high starch content degradable material marked by the successful preparation of the material can be applied to plastic product industries such as ground film and disposable tableware, and it will simultaneously have the performance advantages of low material cost, excellent mechanical strength and biodegradability, and promote the research and development of starch-based degradable materials.
[0088] The present invention will be further described below in conjunction with specific examples. It should be understood that these examples are intended to illustrate the present invention only and are not intended to limit the scope of the present invention. The experimental methods for which specific conditions are not indicated in the following examples are usually performed under conventional conditions (such as the conditions described in Sambrook et al., Molecular Cloning: Laboratory Manual (New York: Cold Spring Harbor Laboratory Press, 1989)) or according to the conditions recommended by the manufacturer. Unless otherwise stated, percentages and parts are weight percentages and weight parts.
[0089] Unless otherwise defined, all professional and scientific terms used herein have the same meanings as those familiar to those skilled in the art. In addition, any methods and materials similar or equivalent to those described herein can be applied to the methods of the present invention. The preferred implementation methods and materials described herein are for demonstration purposes only.
[0090] Example 1
[0091] The high-content starch-based biodegradable composite film of this embodiment is prepared from the following components:
[0092]
[0093] The preparation method thereof comprises the following steps:
[0094] S1: Dry the corn starch granules in an oven at 70°C for 3 hours and store them in a sealed container for later use;
[0095] S2: Place the dried corn starch into an internal mixer, add polyurethane prepolymer, and modify the plant starch. The temperature in the internal mixer is set at 85°C and the mixing time is 30 minutes. Take out the evenly mixed modified starch and place it at room temperature for 14 hours. Use a pulverizer to process the modified starch into 40-mesh particles, and seal them for storage.
[0096] S3: Put the modified starch granules obtained in S2 into a high-speed mixer, add PBAT / PLA composite polyester material with a mass ratio of 10:1, and then add chain extender, reinforcing agent and lubricant. The temperature in the high-speed mixer is controlled at 25°C, the mixing time is 10 minutes, and the mixture is taken out for use after mixing.
[0097] S4: Add the prepared mixed material into the twin screw and set the temperature of each zone respectively. The temperature setting of each zone is as follows:
[0098] District 8 District 7 District 6 District 5 District 4 Zone 3 Zone 2 Zone 1 145℃ 145℃ 150℃ 145℃ 145℃ 140℃ 130℃ 120℃
[0099] Zones 1 and 8 are the front and rear sections, and zones 2 to 7 are the middle sections. Then the twin-screw auxiliary machine is used for strip drawing, water cooling, and granulation to obtain light yellow cylindrical granular raw materials.
[0100] S5: Dry the granular material obtained in S4 in an oven for 4 hours at a temperature of 75°C, and add the dried material into a film blowing machine for film blowing.
[0101] S6: Set the temperature of each zone of the film blowing machine separately. The temperature setting of each zone is as follows:
[0102] District 6 District 5 District 4 Zone 3 Zone 2 Zone 1 150℃ 155℃ 150℃ 145℃ 140℃ 130℃
[0103] Among them, zone 6 is the head part of the film blowing machine, zones 2 to 5 are the middle section, and zone 1 is the front section.
[0104] The starch-based degradable film is obtained by a winding device.
[0105] Example 2
[0106] The high-content starch-based biodegradable composite film of this embodiment is prepared from the following components:
[0107]
[0108]
[0109] The preparation method comprises the following steps:
[0110] S1: Dry the potato starch granules in an oven at 70°C for 3 hours and store them in a sealed container for later use;
[0111] S2: Put the dried potato starch into an internal mixer, add polyurethane prepolymer to modify the plant starch, set the temperature in the internal mixer at 85°C, and mix for 30 minutes. Take out the evenly mixed modified starch, place it at room temperature for 14 hours, and use a pulverizer to process the modified starch into 40-mesh particles, which are sealed and stored for later use.
[0112] S3: Put the modified starch granules obtained in S2 into a high-speed mixer, add PBAT / PLA composite polyester material with a mass ratio of 10:1, and then add chain extender, reinforcing agent and lubricant. The temperature in the high-speed mixer is controlled at 25°C, the mixing time is 10 minutes, and the mixture is taken out for use after mixing.
[0113] S4: Add the prepared mixed material into the twin screw and set the temperature of each zone respectively. The temperature setting of each zone is as follows:
[0114] District 8 District 7 District 6 District 5 District 4 Zone 3 Zone 2 Zone 1 145℃ 145℃ 150℃ 145℃ 145℃ 140℃ 130℃ 120℃
[0115] Zones 1 and 8 are the front and rear sections, and zones 2 to 7 are the middle sections. Then the twin-screw auxiliary machine is used for strip drawing, water cooling, and granulation to obtain light yellow cylindrical granular raw materials.
[0116] S5: Dry the granular material obtained in S4 in an oven for 4 hours at a temperature of 75°C, and add the dried material into a film blowing machine for film blowing.
[0117] S6: Set the temperature of each zone of the film blowing machine separately. The temperature setting of each zone is as follows:
[0118] District 6 District 5 District 4 Zone 3 Zone 2 Zone 1 150℃ 155℃ 150℃ 145℃ 140℃ 130℃
[0119] Among them, zone 6 is the head part of the film blowing machine, zones 2 to 5 are the middle section, and zone 1 is the front section.
[0120] The starch-based degradable film is obtained by a winding device.
[0121] Example 3
[0122] The high-content starch-based biodegradable composite film of this embodiment is prepared from the following components:
[0123]
[0124] The preparation method comprises the following steps:
[0125] S1: Dry the corn starch granules in an oven at 70°C for 3 hours and store them in a sealed container for later use;
[0126] S2: Place the dried corn starch into an internal mixer, add polyurethane prepolymer, and modify the plant starch. The temperature in the internal mixer is set at 85°C and the mixing time is 30 minutes. Take out the evenly mixed modified starch and place it at room temperature for 14 hours. Use a pulverizer to process the modified starch into 40-mesh particles, and seal them for storage.
[0127] S3: Put the modified starch granules obtained in S2 into a high-speed mixer, add PBAT / PLA composite polyester material with a mass ratio of 10:1, and then add chain extender, reinforcing agent and lubricant. The temperature in the high-speed mixer is controlled at 25°C, the mixing time is 10 minutes, and the mixture is taken out for use after mixing.
[0128] S4: Add the prepared mixed material into the twin screw and set the temperature of each zone respectively. The temperature setting of each zone is as follows:
[0129] District 8 District 7 District 6 District 5 District 4 Zone 3 Zone 2 Zone 1 145℃ 145℃ 150℃ 145℃ 145℃ 140℃ 130℃ 120℃
[0130] Zones 1 and 8 are the front and rear sections, and zones 2 to 7 are the middle sections. Then the twin-screw auxiliary machine is used for strip drawing, water cooling, and granulation to obtain light yellow cylindrical granular raw materials.
[0131] S5: Dry the granular material obtained in S4 in an oven for 4 hours at a temperature of 75°C, and add the dried material into a film blowing machine for film blowing.
[0132] S6: Set the temperature of each zone of the film blowing machine separately. The temperature setting of each zone is as follows:
[0133] District 6 District 5 District 4 Zone 3 Zone 2 Zone 1 150℃ 155℃ 150℃ 145℃ 140℃ 130℃
[0134] Among them, zone 6 is the head part of the film blowing machine, zones 2 to 5 are the middle section, and zone 1 is the front section.
[0135] The starch-based degradable film is obtained by a winding device.
[0136] Example 4
[0137] The high-content starch-based biodegradable composite film of this embodiment is prepared from the following components:
[0138]
[0139] The preparation method comprises the following steps:
[0140] S1: Dry the wheat starch granules in an oven at 70°C for 3 hours and store them in a sealed container for later use;
[0141] S2: Put the dried wheat starch into an internal mixer, add polyurethane prepolymer, modify the plant starch, set the temperature in the internal mixer at 85°C, mix for 30 minutes, take out the evenly mixed modified starch, place it at room temperature for 14 hours, use a pulverizer to process the modified starch into 40-mesh particles, and seal them for later use.
[0142] S3: Put the modified starch granules obtained in S2 into a high-speed mixer, add PBAT / PLA composite polyester material with a mass ratio of 4:1, and then add chain extender PBAT, reinforcing agent and lubricant. The temperature in the high-speed mixer is controlled at 25°C, the mixing time is 10 minutes, and the mixture is taken out for use after mixing.
[0143] S4: Add the prepared mixed material into the twin screw and set the temperature of each zone respectively. The temperature setting of each zone is as follows:
[0144] District 8 District 7 District 6 District 5 District 4 Zone 3 Zone 2 Zone 1 145℃ 150℃ 150℃ 145℃ 145℃ 140℃ 130℃ 120℃
[0145] Zones 1 and 8 are the front and rear sections, and zones 2 to 7 are the middle sections. Then the twin-screw auxiliary machine is used for strip drawing, water cooling, and granulation to obtain light yellow cylindrical granular raw materials.
[0146] S5: Dry the granular material obtained in S4 in an oven for 4 hours at a temperature of 75°C, and add the dried material into a film blowing machine for film blowing.
[0147] S6: Set the temperature of each zone of the film blowing machine separately. The temperature setting of each zone is as follows:
[0148] District 6 District 5 District 4 Zone 3 Zone 2 Zone 1 150℃ 155℃ 150℃ 145℃ 140℃ 130℃
[0149] Among them, zone 6 is the head part of the film blowing machine, zones 2 to 5 are the middle section, and zone 1 is the front section.
[0150] The starch-based degradable film is obtained by a winding device.
[0151] Example 5
[0152] The high-content starch-based biodegradable composite film of this embodiment is prepared from the following components:
[0153]
[0154]
[0155] The preparation method comprises the following steps:
[0156] S1: Dry the cassava starch granules in an oven at 70°C for 3 hours and seal them for later use;
[0157] S2: Put the dried cassava starch into an internal mixer, add polyurethane prepolymer to modify the plant starch, set the temperature in the internal mixer at 85°C, and mix for 30 minutes. Take out the evenly mixed modified starch, place it at room temperature for 14 hours, and use a pulverizer to process the modified starch into 40-mesh particles, which are sealed and stored for later use.
[0158] S3: Put the modified starch granules obtained in S2 into a high-speed mixer, add PBAT / PLA composite polyester material with a mass ratio of 9:1, and then add chain extender, reinforcing agent and lubricant. The temperature in the high-speed mixer is controlled at 25°C, the mixing time is 10 minutes, and the mixture is taken out for use after mixing.
[0159] S4: Add the prepared mixed material into the twin screw and set the temperature of each zone respectively. The temperature setting of each zone is as follows:
[0160] District 8 District 7 District 6 District 5 District 4 Zone 3 Zone 2 Zone 1 145℃ 145℃ 150℃ 145℃ 145℃ 140℃ 130℃ 120℃
[0161] Zones 1 and 8 are the front and rear sections, and zones 2 to 7 are the middle sections. Then the twin-screw auxiliary machine is used for strip drawing, water cooling, and granulation to obtain light yellow cylindrical granular raw materials.
[0162] S5: Dry the granular material obtained in S4 in an oven for 4 hours at a temperature of 75°C, and add the dried material into a film blowing machine for film blowing.
[0163] S6: Set the temperature of each zone of the film blowing machine separately. The temperature setting of each zone is as follows:
[0164] District 6 District 5 District 4 Zone 3 Zone 2 Zone 1 150℃ 155℃ 150℃ 145℃ 140℃ 130℃
[0165] Among them, zone 6 is the head part of the film blowing machine, zones 2 to 5 are the middle section, and zone 1 is the front section.
[0166] The starch-based degradable film is obtained by a winding device.
[0167] Example 6
[0168] The high-content starch-based biodegradable composite film of this embodiment is prepared from the following components:
[0169]
[0170] The preparation method comprises the following steps:
[0171] S1: Dry the corn starch granules in an oven at 70°C for 3 hours and store them in a sealed container for later use;
[0172] S2: Place the dried corn starch into an internal mixer, add polyurethane prepolymer, and modify the plant starch. The temperature in the internal mixer is set at 85°C and the mixing time is 30 minutes. Take out the evenly mixed modified starch and place it at room temperature for 14 hours. Use a pulverizer to process the modified starch into 40-mesh particles, and seal them for storage.
[0173] S3: Put the modified starch granules obtained in S2 into a high-speed mixer, add PBAT / PLA composite polyester material with a mass ratio of 4:1, and then add chain extender, reinforcing agent and lubricant. The temperature in the high-speed mixer is controlled at 25°C, the mixing time is 10 minutes, and the mixture is taken out for use after mixing.
[0174] S4: Add the prepared mixed material into the twin screw and set the temperature of each zone respectively. The temperature setting of each zone is as follows:
[0175] District 8 District 7 District 6 District 5 District 4 Zone 3 Zone 2 Zone 1 145℃ 150℃ 150℃ 145℃ 145℃ 140℃ 130℃ 120℃
[0176] Zones 1 and 8 are the front and rear sections, and zones 2 to 7 are the middle sections. Then the twin-screw auxiliary machine is used for strip drawing, water cooling, and granulation to obtain light yellow cylindrical granular raw materials.
[0177] S5: Dry the granular material obtained in S4 in an oven for 4 hours at a temperature of 75°C, and add the dried material into a film blowing machine for film blowing.
[0178] S6: Set the temperature of each zone of the film blowing machine separately. The temperature setting of each zone is as follows:
[0179] District 6 District 5 District 4 Zone 3 Zone 2 Zone 1 150℃ 155℃ 150℃ 145℃ 140℃ 130℃
[0180] Among them, zone 6 is the head part of the film blowing machine, zones 2 to 5 are the middle section, and zone 1 is the front section.
[0181] The starch-based degradable film is obtained by a winding device.
[0182] The materials obtained in Examples 1 to 6 are numbered X1 to X6, respectively.
[0183] The materials of Examples 1 to 6 were subjected to Fourier infrared testing. The results are as follows: Figure 1 shown.
[0184] from Figure 1 It can be seen that the material has an infrared wavelength of 3400cm -1 There is no infrared peak here, which is the hydroxyl peak in starch. Therefore, there are no active hydroxyl groups in the material, which helps to improve the overall hydrophobic properties of the material.
[0185] The biodegradable films numbered X1 to X6 were subjected to tensile mechanical property tests using 4×25 mm dumbbell-shaped specimens according to the GB / T 1040.3-2006 test standard. The test results are shown in Table 1 below.
[0186] Table 1: Mechanical properties of starch-based biodegradable composite films numbered X1 to X6
[0187]
[0188] As shown in Table 1, the samples obtained according to the materials and preparation methods of the present invention have good mechanical properties, with elongation at break exceeding 750% and tensile strength exceeding 14 MPa. By combining the change in the proportion of polyester materials and the change in the auxiliary agent, the purpose of increasing the starch content can be achieved while ensuring the mechanical properties.
[0189] The surface morphology of the film of Example 1 of the present invention was observed under a scanning electron microscope, and the results obtained are as follows Figure 2 shown.
[0190] from Figure 2 It can be seen that the surface of the sample is smooth and flat, without surface defects such as protrusions or depressions, which helps to maintain good mechanical properties.
[0191] like Figure 3 , Figure 4 As shown, the film forming process of the present invention is smooth and uniform, and the prepared film material has good flatness and transparency.
[0192] All documents mentioned in the present invention are cited as references in this application, just as each document is cited as reference individually. In addition, it should be understood that after reading the above teachings of the present invention, those skilled in the art can make various changes or modifications to the present invention, and these equivalent forms also fall within the scope defined by the claims attached to this application.
Claims
1. A starch-based plastic film, characterized in that: Contains the following ingredients:
2. The starch-based plastic film according to claim 1, characterized in that: The plant starch is at least one of potato starch, corn starch, wheat starch, tapioca starch and pea starch.
3. The starch-based plastic film according to claim 1, characterized in that: The polyurethane prepolymer is prepared by reacting one of polyethylene adipate glycol, polycaprolactone glycol, polytetramethylene ether glycol, polybutylene adipate glycol and polybutylene succinate glycol with one of diphenylmethane diisocyanate, hexamethylene diisocyanate and toluene diisocyanate.
4. The starch-based plastic film according to claim 1, characterized in that: The isocyanate content of the polyurethane prepolymer is 3wt%-10wt%.
5. The starch-based plastic film according to claim 1, characterized in that: The composite polyester comprises polybutylene adipate / terephthalate (PBAT) and polylactic acid (PLA), wherein the mass percentage of PBAT is 70%-99% of the total amount of the composite polyester material, and the mass percentage of PLA is 1%-30% of the total amount of the composite polyester material.
6. The starch-based plastic film according to claim 1, characterized in that: The compatibilizer is at least one of citric acid, maleic anhydride, grafted PBAT, chain extended PBAT, chain extended ADR-4370, chain extended ADR4468, chain extended KL-E4370, chain extended KL-E4370B, chain extended KS-05, chain extended XY4370, and chain extended SAG-008.
7. The starch-based plastic film according to claim 1, characterized in that: The reinforcing agent is at least one of attapulgite, nano silicon dioxide, nano calcium carbonate, nano zinc oxide, bentonite, halloysite and montmorillonite.
8. The starch-based plastic film according to claim 1, characterized in that: The lubricant is at least one of Tween, calcium stearate, magnesium stearate, erucic acid amide, erucic acid amide, and docosenoic acid amide.
9. The method for preparing a starch-based plastic film according to claim 1, characterized in that: The following steps are involved: S1: Dry the plant starch and store it in a sealed container for later use; S2: Put the dried plant starch into an internal mixer, add the polyurethane prepolymer, modify the plant starch, use a pulverizer to process the modified starch into particles of 20-60 meshes, and seal and store them for later use; S3: putting the modified starch granules obtained in S2 into a high-speed mixer, adding the composite polyester, and then adding the compatibilizer, reinforcing agent, and lubricant, mixing evenly and then taking out for use; S4: adding the mixed material prepared in S3 into a twin-screw extruder for extrusion, and then drawing, water-cooling, and granulating on a twin-screw auxiliary machine to obtain a light yellow cylindrical granular material; S5: drying the granular material obtained in S4 and adding it to a film blowing machine for film blowing, and obtaining a starch-based biodegradable film through a winding device.
10. The preparation method according to claim 9, characterized in that: The preparation method includes one or more of the following features: (1) drying the plant starch in an oven at 60°C-80°C for 3-6 hours; (2) The temperature in the internal mixer is set at 80°C-100°C and the mixing time is 20min-45min; (3) The modified starch evenly mixed in the internal mixer is taken out and placed at room temperature for 12 h to 24 h; (4) The temperature in the high-speed mixer is controlled at 20°C-40°C, and the mixing time is 5min-15min; (5) The feeding section temperature of the twin-screw extruder is set to 120°C-130°C, the middle section temperature is set to 130°C-155°C, and the head section temperature is set to 140°C-160°C; (6) The granular material obtained in S4 is dried in an oven for 4 h to 6 h, and the temperature in the oven is 60° C. to 80° C.; (7) The temperature of the die head of the film blowing machine in S5 is 140°C-160°C, the temperature of the machine body is 130°C-155°C, and the film blowing temperature is 140°C-150°C.
Citation Information
Patent Citations
Continuously-produced full-degradable starch-based plastic alloy and preparation method thereof
CN103992517A
Starch-based degradable material and preparation method and application thereof
CN111040392A
Starch modified PBAT / PLA biodegradable plastic film and preparation method thereof
CN113861635A